Organização governamental e trabalho: auto-realização, prazer e eficácia - o caso da Escola de Artes Visuais do Parque Lage - Carvalho, Paulo Roberto Barros de (1998)
The objective of this research is to examine how motivation in a governmental organization engaged with the Arts activities since its early existence deals with categories as auto-realization, pleasure and eficacy in working, in accordance with what their members think about that. The first chapter concerns to the theoretical reference that has taken place in the study. The second chapter tell us about historical data of the region where the organization is situated, as well as its early existence most important information and subsequent trajetory. The third chapter describes the main characteristics of the organization as the result of the research instrument that had been answered by their members. Finally, we can find the conclusions of the research, when comparing the theoretical considerations of the chosen authors face to face to the results of the interviews that had taken place in the Escola de Artes Visuais do Parque Lage - certainly the most important Brazilian Contemporary Art reference organization.